Costs of delivering human papillomavirus vaccination using a one- or two-dose strategy in Tanzania. Issue 2 (9th January 2023) - Hsiao, Amber; Struckmann, Verena; Stephani, Victor; Mmbando, Devis; Changalucha, John; Baisley, Kathy; Levin, Ann; Morgan, Winthrop; Hutubessy, Raymond; Watson – Jones, Deborah; Whitworth, Hilary; Quentin, Wilm
Abstract: Objective: As part of the Dose Reduction Immunobridging and Safety Study of Two HPV Vaccines in Tanzanian Girls (DoRIS; NCT02834637), the current study is one of the first to evaluate the financial and economic costs of the national rollout of an HPV vaccination program in school-aged girls in sub-Saharan Africa and the potential costs associated with a single dose HPV vaccine program, given recent evidence suggesting that a single dose may be as efficacious as a two-dose regimen. Methods: The World Health Organization's (WHO) Cervical Cancer Prevention and Control Costing (C4P) micro-costing tool was used to estimate the total financial and economic costs of the national vaccination program from the perspective of the Tanzanian government. Cost data were collected in 2019 via surveys, workshops, and interviews with local stakeholders for vaccines and injection supplies, microplanning, training, sensitization, service delivery, supervision, and cold chain. The cost per two-dose and one-dose fully immunized girl (FIG) was calculated. Results: The total financial and economic costs were US10, 117, 455 and US45, 683, 204, respectively, at a financial cost of 5.17 per two-dose FIG, and an economic cost of 23.34 per FIG. Vaccine and vaccine-related costs comprised the largest proportion of costs, followed by service delivery. In a one-dose scenario, the cost per FIG reduced to 2.51 (financial) and 12.18 (economic), with the largest reductions in vaccine and injection supply costs, and service delivery. Conclusions: The overall cost of Tanzania's HPV vaccination program was lower per vaccinee than costs estimated from previous demonstration projects in the region, especially in a single-dose scenario. Given the WHO Strategic Advisory Group of Experts on Immunization's recent recommendation to update dosing schedules to either one or two doses of the HPV vaccine, these data provide important baseline data for Tanzania and may serve as a guide for improving coverage going forward. The findings may also aid in the prioritization of funding for countries that have not yet added HPV vaccines to their routine immunizations.